Physiological health parameters among college students to promote chronic disease prevention and health promotion - David R. Black; Daniel C. Coster; Samantha R. Paige (Preventive Medicine Reports, 2017)
This study aimed to provide physiologic health risk parameters by gender and age among college students enrolled in a U.S. Midwestern University to promote chronic disease prevention and ameliorate health. A total of 2615 college students between 18 and 25 years old were recruited annually using a series of cross-sectional designs during the spring semester over an 8-year period. Physiologic parameters measured included body mass index (BMI), percentage body fat (%BF), blood serum cholesterol (BSC), and systolic (SBP) and diastolic (DBP) blood pressure. These measures were compared to data from NHANES to identify differences in physiologic parameters among 18–25 year olds in the general versus college-enrolled population. A quantitative instrument assessed health behaviors related to physical activity, diet, and licit drug use. Results suggest that average physiologic parameters from 18 to 25 year olds enrolled in college were significantly different from parameters of 18–25 year olds in the general population. Generally, men reported higher percentiles for BMI, SBP, and DBP than women, but lower %BF and BSC percentiles than women at each age. SBP and DBP significantly increased with age and alcohol use. Students in the lowest (5th) and highest percentiles (95th and 75th), for most age groups, demonstrated DBP, BMI, and %BF levels potentially problematic for health and future development of chronic disease based on percentiles generated for their peer group. Newly identified physiologic parameters may be useful to practitioners serving college students 18–25 years old from similar institutions in determining whether behavior change or treatment interventions are appropriate.